Communication and effectiveness in a US nursing home quality‐improvement collaborative. (21st November 2013) - Arling, Priscilla A.; Abrahamson, Kathleen; Miech, Edward J.; Inui, Thomas S.; Arling, Greg
Abstract In this study, we explored the relationship between changes in resident health outcomes, practitioner communication patterns, and practitioner perceptions of group effectiveness within a quality‐improvement collaborative of nursing home clinicians. Survey and interview data were collected from nursing home clinicians participating in a quality‐improvement collaborative. Quality‐improvement outcomes were evaluated using US Federal and State minimum dataset measures. Models were specified evaluating the relationships between resident outcomes, staff perceptions of communication patterns, and staff perceptions of collaborative effectiveness. Interview data provided deeper understanding of the quantitative findings. Reductions in fall rates were highest in facilities where respondents experienced the highest levels of communication with collaborative members outside of scheduled meetings, and where respondents perceived that the collaborative kept them informed and provided new ideas. Clinicians observed that participation in a quality‐improvement collaborative positively influenced the ability to share innovative ideas and expand the quality‐improvement program within their nursing home. For practitioners, a high level of communication, both inside and outside of meetings, was key to making measurable gains in resident health outcomes.